Religion and Ideology - George Pittappillil (Journal of Dharma, 1977)
Dr. F, Houtart's book. Religion and Ideology, Sri Lanka has already caught the attention of many interested readers. The book presents the penetrating research of Dr. Houtart into the interactions of the religious, political and economic ideologies of Sri Lanka.